CO2 storage potential in sedimentary basins of Kazakhstan. (December 2020) - Abuov, Yerdaulet; Seisenbayev, Nurlan; Lee, Woojin
Highlights: Precaspian, Mangyshlak, South Torgay and Ustyurt basins are suitable for CCS. CCS has potential to safely store 539 Gt CO2 in Kazakhstan. With CO2 -EOR deployment, Kazakhstan has a huge potential for CCS. CCS can help Kazakhstan to reach the targets set by the Paris Agreement. Abstract: The terms of the Paris Agreement oblige Kazakhstan to decrease its Greenhouse Gas (GHG) emissions by 2030. Annual GHG emissions of the country already went beyond the limit set by the Paris agreement in 2014 and this number is expected to increase with a growing economy showing that current measures of GHG mitigation in the country are insufficient. Despite the energy sector of the country being heavily dependent on its coal and substantial land resources, CCS was not featured in the "Green Economy" plan of the country. To investigate the applicability of this technology, six selected Kazakhstan sedimentary basins (the Precaspian, Mangyshlak, South-Torgay, Ustyurt, Chu-Sarysu, and Zaysan basins) were evaluated and ranked for geologic CO2 storage deployment in terms of containment, capacity, and feasibility. The effective CO2 storage capacities in oil reservoirs, gas reservoirs, and saline aquifers were estimated for each basin using the Carbon Sequestration Leadership Forum (CSLF) and USDOE methods. The evaluations revealed that the Precaspian Basin is the most suitable for geological CO2 storage, followed by the Mangyshlak, South Torgay, and Ustyurt basins. The total effective CO2 storage capacity of the country is estimated to be ∼583 Gt, of which ∼539 Gt corresponds to the abovementioned four suitable basins where most of injected CO2 is expected to be stored in the hydrodynamic traps. The results suggest that four sedimentary basins identified in this study have prospectivity to reduce GHG emissions of Kazakhstan significantly and thus enable the decarbonization of national economy to achieve the goals set by the Paris Agreement.